What to include in a Review, Commentary, Editorial, and Special Edition of Global Health Management Journal - Andrew John Macnab (GHMJ (Global Health Management Journal), 2023)
There are several different types of article that authors can submit for publication in a journal. The article types are intended to allow for original research, commentaries, and reviews that are relevant to the stated focus and scope of the journal to be presented to the readers in an interesting and informative manner. Some journals have a special interest in less common forms of communication, and so will accept submissions to other categories, such as interesting images, videos, case reports, or descriptions of teaching methods or learning points. Authors should read the instructions and their editorial policies for authors section on each journal's website to identify the types of article the editorial team will consider, and then prepare their submission to comply with the description given for each type of article and specific instructions on how each should be formatted. This editorial describes three categories of article and their guidelines to be included in the Global Health Management Journal: Editorial, Commentary and Review. To provide more exposure of papers and works presented at international forums, seminars, and conferences, the journal creates specific guidelines to publish the selected papers from the meetings in Global Health Management Journals as a Special Edition.